The Relationship between Family Functions and the Quality of Life of the Elderly with Hypertension in the working area Public Health Center of Babadan - Oktaviani, Dinta Sekar; Anggraini, Merry Tiyas; Noviasari, Nina Anggraeni (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Hypertension is still a major problem in the elderly at the Babadan Health Center, based on data in 2021 the incidence of hypertension at the Babadan Health Center is 539 cases. Due to the high rate of hypertension in the elderly, it has a negative impact on the quality of life. Elderly who suffer from hypertension need the role of a good family function in order to create a good quality of life as well. The general purpose of this study was to explain the relationship between family functions and the quality of life of elderly patients with hypertension in the working area of Babadan Health Center.Methods: Analytical observational research with cross sectional approach and using simple random sampling technique. This research was conducted from October to December 2021 in the working area of the Babadan Health Center, Ponorogo Regency. The number of samples for this study was 67 samples with inclusion criteria and exclusion criteria. Data collection was obtained from the results of filling out the APGAR Family questionnaire and the WHOQOL-BREF questionnaire which had been tested for validity and reliability. The data obtained were analyzed with bivariat analysis used Chi-Square test.Results: The majority of elderly people with hypertension at the Babadan Health Center have healthy family functions and a good quality of life, especially in the domain of social relations. Based on statistical analysis using the Chi-Square test, it was found that there was a significant relationship between family function and the quality of life of the elderly with hypertension (p = 0.000; PR = 8.9; CI = 95% 2.954 to 26.830).Conclusion: Elderly people with hypertension who come from healthy families are 9 times more likely to have a good quality of life than the elderly who come from unhealthy families. The role of a good family function will affect the quality of life of elderly people with hypertension, especially in terms of social relationships.